PRESUMPTION OF INNOCENCE AS AN IMPORTANT RULE OF THE UNIVERSAL DECLARATION OF HUMAN RIGHTS - Matkarimov Kudrat Kalandarovich (Scholar Express Journals, 2023)
In this study, the author presented an analysis of the presumption of innocence and the international legal norms of the Universal Declaration of Human Rights. He paid special attention to the importance and improvement of the mechanism of compliance with international legal norms in the field of justice and its reflection in national legislation. In addition, the author gave reasonable explanations regarding the improvement of national legislation in connection with international law norms.
Keywords: Presumption of innocence; human rights; international law; international fair trial